Gestão de recursos do poder legislativo municipal: estudo para o município de Eusébio-CE - Mota, Giordano Bruno Araújo Cavalcante (2009)
Theworld market undermined by increasingly negative information about the financial health of many global companies, exposing the fragility of the controls as well as the supervision carried out by institutions that should control them.The search for mechanism by wich companies seek to correct devations and the optimization of processes to the efficiency of actions, reflects a sense that has been seen for a long time in the public sphere.The pressure made by institutions and society forces the Government to adopt programs that makes the management of their resources more efficient. We can not talk about efficiency without addressing the influence of control, the control in general, especially the internal control is brought to the center of discussions. The fiscalization made by the Municipal Legislative Power, and the courts auditors, are focused on the deployment and implementation of internal controls.In this context the present thesis aims the development of the model for the management of resources, comprising the elaboration of the flow of expenditures and the specification of operational procedures, to the attention of legal proceedings, to obtain more reliable information and the strengthening of controls. The method of case study was applied to the Eusebio Municipal Council with literature research and documents relevant to the subject, and general information on application of questionnaires and interviews with current Councilors.The collected data shows that, although the Councilors recognizes the importance of the effectiveness of internal control as a means to achieve better results in the counts audited by courts, they have a limited level of knowledge on the subject. Form this model the Eusebio Municipal Council may adopt operational procedures of control, and support for management decisions wich enable a more rational use of resources available.